GC-MS Analysis, Phytochemical Screening and Biological Activity of Bauhinia tomentosa (Linn.) - Mini, R.; Prabhu, V.; Vimaladevi, K.; Sowmiya, J.; Sibi, G. (Asian Journal of Chemistry, 2021)
Present study aimed to evaluate the chemical composition and biological activity for methanolic extract of Bauhinia tomentosa (Linn.) leaves grown in Western Ghats region of South India. The preliminary phytochemical screening tests revealed the presence of steroids, alkaloids, terpenoids, flavonoids, glycosides and phenolic compounds in the leaf extract. A total of 19 compounds were identified through gas chromatography-mass spectroscopy (GC-MS) analysis of methanolic extract of B. tomentosa. The major compounds identified were phytol (23.96%), n-hexadecanoic acid (11.62%), squalene (8.85%) and the minor compounds are trans-bis(2-methylpropyl)-4,6-dioxane(0.13%), dihydro-cis-α-copaene-8-ol (0.14%), tetradecanoic acid (0.81%), respectively. Antibacterial activity of the extract showed the zone of inhibition 18 mm at 200 μg/mL against S. aureus, followed by 15 and 16 mm against S. anginosus, K. pneumoniae at 200 μg/mL, respectively. Antioxidant activity of methanolic extract of B. tomentosa leaves showed the maximum IC50 value with 75.07 % of scavenging activity at the concentration of 5 μg/mL.